Intranasal Dexmedetomidine increases the successful sedation of children with autism for out-patient auditory brainstem response hearing tests. (December 2021) - Luque, Carolina Grau; Atkins-Labelle, Cheryl; Pauwels, Julie; Costello, Rhodri; Kozak, Frederick K.; Chadha, Neil K.
Abstract: Introduction: The auditory brainstem response (ABR) hearing test can be challenging in children with autism spectrum disorder (ASD) due to the inherent behavioral challenges associated with this condition. To attempt to increase our success in sedating ASD patients, we added the use of intranasal Dexmedetomidine (Dexmed) to be used alone or with oral Chloral Hydrate (CH) in an ambulatory care setting, with monitoring by a specialist nurse. Objectives: To determine the success and safety of a protocol for ABR testing performed under sedation with intranasal Dexmed and oral chloral hydrate in ASD patients. To compare the success rate, the occurrence of adverse events and time needed to initiate ABR between Dexmed-CH protocol and previous CH-alone protocol in ASD patients. Methods: Retrospective review. ASD patients in Dexmed-CH sedation protocol were age- and sex-matched to ASD patients who underwent CH-alone sedation protocol, for comparison. Results: 74 ABR records in ASD children were included, 37 patients using Dex-CH protocol and 37 patients using CH-alone protocol. In the Dexmed-CH protocol group, Dexmed was used in 2 different ways: alone as a first choice in patients who refused to swallow CH (9/37), or combined with CH as a rescue (28/37). Under this sedation protocol, 89% of the attempted ABRs were completed successfully with no major adverse effects. In comparison, in ASD patients sedated using the protocol of CH-alone, the success rate significantly lower (69% vs. 89%). The time needed to initiate the test was not significantly different. Conclusion: The use of intranasal Dexmed by itself or in combination with CH was a safe and reliable method of performing sedated ABR in ASD patients. Modifying our previous oral CH protocol to include intranasal Dexmed, substantially improved our success rate of sedation in ASD patients in an ambulatory setting. This study may be of significant value to centers worldwide exploring alternatives to general anesthesia for ABR testing in ASD patients. Highlights: Intranasal Dexmedetomidine, alone or combined with oral Chloral Hydrate, improved success of sedation in ASD patients. Intranasal Dexmedetomidine was shown to be a safe and reliable method of performing sedated ABR in children with autism. Intranasal Dexmedetomidine can be used as an alternative to general anesthesia for ABR testing in ASD patients.